PKM Konveksi Sebagai Sarana Pengembangan Industri Kreatif Di Desa Kebonagung Kecamatan Pakisaji Kabupaten Malang - Kusubakti Andajani; Endang Sri Andayani; Retno Wulandari, ST., MT (STIE Malangkucecwara, 2021)
UMKM convection is a business that must be strengthened in relation to the implementation of the MEA. Srawung Convection UMKM which are partners for the Community Partnership Program have existed in Kebonagung Village, Pakisaji District, Malang Regency since 2014. The existence of Srawung Convection UMKM is very much felt by Vocational High Schools (SMK) in the City and District of Malang as an internship place to train clothing making skills t-shirts/t-shirts. Thus indirectly the existence of Srawung Convection UMKM helps overcome unemployment in the City and Regency of Malang through the creation of new t-shirt convection business actors. The problems that were agreed with Srawung Convection UMKM were: 1) Production aspects and 2) Economic aspects. Based on the results of the meeting and joint coordination with the Srawung Convection UMKM, it was agreed that the above problems were resolved by the following methods: 1) Convection UMKM Productivity Improvement Program which included: procurement and training of single needle sewing machines, procurement and training of chain sewing machines, and cloth cutting machines and 2) Convection UMKM Management Aspect Improvement Program which includes: business management training, production management training, marketing training, production planning training, financial management training, inventory training, marketing training, and HR management training. The results of the implementation of the PKM program: 1) The productivity of Srawung Convection UMKM increased by 100%, 2) The ability of the management aspects of Srawung Convection UMKM increased by 100%